Innovation system for sustainability in developing countries: the renewable energy sector in Bolivia. (15th February 2013) - Pansera, Mario
The paper describes the main ideas surrounding the topic of innovation for sustainability in developing countries. Innovation is a crucial element to foster sustainability as well as an egalitarian development. The work illustrates that sustainable development is possible by exploiting local potential and traditional knowledge in order to achieve at the same time economic growth, social equality and environmental sustainability. In order to prove such an assumption a specific case study is described: the renewable energy sector in Bolivia. The case study analyses several dimensions of the innovation process in developing countries such as technological transfer, diffusion and adaptation, social dimension and development issues. The Bolivian case showed that it is possible to foster sustainability and local entrepreneurship by triggering the endogenous energies embedded in territories and traditional knowledge.